LEGAL PROTECTION FOR THIRD PARTIES DUE TO VIOLATIONS OF ARTICLE 30 OF GOVERNMENT REGULATION NUMBER 24 OF 1997 CONCERNING LAND REGISTRATION - Rian Mangapul Sirait (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
Land registration is an important legal instrument in the Indonesian land law system aimed at providing legal certainty and legal protection for holders of land rights. Article 30 of Government Regulation No. 24 of 1997 regulates the obligation to announce physical data and juridical data in the land registration process in order to protect the interests of third parties. However, in practice, violations of this provision are still found, which harm third parties acting in good faith. This research employs a normative juridical method with a statutory approach and a case approach to analyze three main issues: the regulation of Article 30 of Government Regulation No. 24 of 1997, the forms of its violations, and the mechanisms of legal protection for disadvantaged third parties. The results show that violations of Article 30 may take the form of failure to carry out announcements, inadequate announcements, or fictitious announcements. Legal protection for third parties can be pursued through preventive mechanisms (supervision and participation in the announcement process) and repressive mechanisms (lawsuits for certificate cancellation, compensation, and administrative sanctions). This study recommends strengthening supervision, digitalizing the announcement system, and increasing public legal awareness.